2017
DOI: 10.3892/ol.2017.6361
|View full text |Cite
|
Sign up to set email alerts
|

Wip1 gene silencing enhances the chemosensitivity of human colon cancer cells

Abstract: Abstract. Colon cancer is one of the most common cancers in the world. Multidrug resistance is one of the main reasons for failure of therapy in patients with advanced colon cancer. In previous studies, multiple methods were investigated to reverse the multidrug resistance of colon cancer cells. However, to date, no clinical method has been identified to be satisfactory. Therefore, successful reversal of drug resistance in colon cancer cells still requires new therapeutic strategies or pharmaceuticals. Wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…These findings suggest that Wip1 may be involved in chemoresistance in the advanced disease of OCCC, as TFI is well known to be an important surrogate marker for the chemosensitivity in ovarian cancer [ 24 26 ]. This hypothesis may be supported by the published findings that Wip1 is involved in chemoresistance in other types of cancer cells [ 27 , 28 ]. Chemoresistance is known to be related with low activity of cellular proliferation.…”
Section: Discussionsupporting
confidence: 60%
“…These findings suggest that Wip1 may be involved in chemoresistance in the advanced disease of OCCC, as TFI is well known to be an important surrogate marker for the chemosensitivity in ovarian cancer [ 24 26 ]. This hypothesis may be supported by the published findings that Wip1 is involved in chemoresistance in other types of cancer cells [ 27 , 28 ]. Chemoresistance is known to be related with low activity of cellular proliferation.…”
Section: Discussionsupporting
confidence: 60%
“…cc is a common malignant gastrointestinal tumor; ~20% of patients suffer from liver metastasis after treatment, and the 3-year survival rate of these patients is 5% (23,24). Therefore, it is important to explore novel effective therapeutic options for cc treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that targeting Wip1 enhances sensitivity to chemotherapy and promotes apoptosis in human cancers harboring wt p53. However, contradictory data have been reported for p53-deficient tumors (23,25). For example, the study conducted by Goloudina et al (23) demonstrated that the inhibition of Wip1 increased the sensitivity of wt p53 HCT116 colon cancer cells to cisplatin-induced apoptosis, but did not have such an effect on p53 -/-HCT116 or Saos-2 cells.…”
Section: Discussionmentioning
confidence: 99%